DOMINASI PENGUASA KOLONIAL TERHADAP BUMIPUTRA DALAM SURAT KERAJAAN PONTIANAK ABAD KE-19: ANALISIS PASCAKOLONIAL - Bagus Kurniawan (POETIKA, 2013)
AbstractProcess of colonialism in a long archipelago led to a number of colonial domination colonizers against thecolonized. It can be seen in the classical Malay literature. Slightly, it is different from the concept of literature in themodern sense, in the sense of classical Malay literature, including royal scripts as a literary work. Therefore, the localroyal scripts archipelago in the 18th century period 19th addressed to the colonial power are a classical Malay literatureto inform the colonial domination of the colonized people. As such, this paper outlines the dominance of colonial powersagainst colonized peoples contained in the classical Malay literature, especially the royal letter. Royal scripts that serve asthe object of study in this paper is a letter sent Pontianak Royal Prince Syarif Abu Bakar Al Qadri to JF Walrave vanNes, dated May 16, 1847. The script indicates the inequality relationship between the subjects with the object. Colonialauthorities have the power to regulate and dominate the native people. Relations between the Kingdom of Pontianakwith no colonial power relations that have the same bargaining power politics, and the Kingdom of Pontianak act as aparty dominated politically, and economically. Therefore, the Pontianak Kingdom of the letter will be analyzed throughpostcolonial theory to see a picture of the condition of literary colonialism Kingdom of Pontianak in the 19th century.Keywords: colonialism, domination, royal scripts, postcolonial